2002
DOI: 10.1177/014107680209501004
|View full text |Cite
|
Sign up to set email alerts
|

Health Status and Clinical Diagnoses of 3000 UK Gulf War Veterans

Abstract: Up to June 2001, 3000 British veterans of the Gulf War had sought advice from a special medical assessment programme established because of an alleged Gulf War syndrome. After assessment those attending were classified as completely well, well with symptoms, well with incidental diagnoses treated or controlled, or unwell (physically or mentally). Mental illness was confirmed by a psychiatrist. The first 2000 attenders have been reported previously. The present paper summarizes findings in all 3000. 2252 (75%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…An analysis of death certificates also showed that veterans with post-combat syndromes did not develop a particular organic illness or suffered an increased mortality (Grant 1925;Kang & Bullman 2001;Jones et al 2003b). This symptom-based investigation confirmed epidemiological and clinical studies that there is no unique illness related to service in the Gulf in 1991 (Unwin 1999;Lee et al 2002) and yet the term 'GWS' continues to enjoy popular support (Lloyd 2004, pp. 41, 56, 57).…”
Section: Gulf War Syndromesupporting
confidence: 62%
“…An analysis of death certificates also showed that veterans with post-combat syndromes did not develop a particular organic illness or suffered an increased mortality (Grant 1925;Kang & Bullman 2001;Jones et al 2003b). This symptom-based investigation confirmed epidemiological and clinical studies that there is no unique illness related to service in the Gulf in 1991 (Unwin 1999;Lee et al 2002) and yet the term 'GWS' continues to enjoy popular support (Lloyd 2004, pp. 41, 56, 57).…”
Section: Gulf War Syndromesupporting
confidence: 62%
“…This group was selected because PTSD was the most frequent diagnosis amongst the unwell. 9,10 None of these veterans had organic disease that could have biased the results. This group was specifically analysed because of reports suggesting low serum cortisol concentrations in such patients.…”
Section: Blood Testsmentioning
confidence: 99%
“…10 They were analysed for any abnormalities. This study was undertaken as claims had been made by some veterans' groups that there was an increased incidence of liver and renal scarring.…”
Section: Ultrasound Studies Of Abdominal Visceramentioning
confidence: 99%
“…The most commonly reported symptoms included fatigue, headaches, joint pains, skin rash, shortness of breath, sleep disturbances, difficulty concentrating, depression and forgetfulness (DeFraites et al 1992;Persian Gulf Veterans Coordinating Board 1995). Subsequently, there were reports of British, Canadian and Australian veterans with similarly idiopathic symptoms (Goss Gilroy, Inc & Canadian Department of National Defence 1998; Ikin et al 2004;Lee et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to concerns about the health of Gulf War veterans, the US Department of Veterans Affairs (VA) and Department of Defense (DoD) and the British and Canadian Ministries of Defence established special clinical evaluation programmes to assess veterans' health problems (Joseph et al 1998;Lee et al 2002). To date over 100 000 veterans have been systematically evaluated in these programmes (Department of Veteran Affairs 2002).…”
Section: Introductionmentioning
confidence: 99%